Pengembangan Model Media Video pada Pembelajaran Praktik Pemesinan Bubut - Ridwan Oktavian Hananta; Thomas Sukardi (Department of Mechanical Engineering Education, 2018)
This study aims to examine the development and the usability of a video-based learning media on the subject of lathe metric threading. The study was carried out in class XI of Machining program study. This research is a Research and Development using ADDIE (Analysis-Design-Development-Implement-Evaluation) learning design. Data collection techniques that was used were questionnaires and research documentation. The development process of video models is carried out by observation and validation from material experts, media experts and subject teachers. The development of the media resulted in the video-based learning media products in the form of an mp4 video formats. The evaluation of the video media resulted in an average usability of 78.85%, which lies in the